DEGRADASI METIL VIOLET MENGGUNAKAN KATALIS ZnO-TiO2 SECARA FOTOSONOLISIS - Hary Sanjaya (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
Research on the degradation of methyl violet has been done by using photosonolysis method. The purpose of this study is to determine how much time the optimum, optimum pH and the amount of doping TiO2 optimum degrade methyl violet as well as the percent degradation, determined the crystal structure and particle size of the catalyst synthesis of ZnO-TiO2 optimum degrade methyl violet using XRD, determine the value of the band gap Of the optimum ZnO-TiO2 catalyst synthesis in degrading methyl violet using UV-DRS, determining the absorption peak of Zn-O-Ti bonds from optimum ZnO-TiO2 catalyst synthesis in degrading methyl violet using FTIR. The results showed that the optimum time to degrade methyl violet was 45 minutes with 94,1371% degradation percentage. For pH variation, the optimum degradation results at pH 6 with percent degradation of 99.2857%. The effect of TiO2 doping variation showed optimum degradation result obtained on doping variation of TiO2 5% with percentage degradation of 96,2500%. The optimum catalyst structure of ZnO-TiO2 catalyst in degrading methyl violet with XRD is wurtzite (anatase) and the particle size is 42.65 - 107.60 nm. The band gap value of the optimum ZnO-TiO2 catalyst in degrading methyl violet with UV-DRS is 3.18 eV. The absorption peak of ZnO-Ti for optimum catalyst ZnO-TiO2 in degrading methyl violet with FTIR is 745.70 cm-1.